SUBAK MEMADUKAN NILAI TRADISIONAL DAN MODERN - Wayan Sudarta (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2018)
The research aims to (1) analyze subak which is loaded with traditional values, but accepts modern ideas, and (2) analyzes their implementation in the field, that subak combines traditional and modern values in cultivating food crops in rice fields. The results of the study show the following. (1) Subak is loaded with traditional values, but accepts modern values. This happens because subak is flexible or dynamic and has adopted modern values. (2) Subak combines traditional and modern values seen in the implementation of Nangluk Merana (traditional values) and the application of Integrated Pest Management (modern value) in integrated pest control in rice cultivation.